Respostas
respondido por:
2
quando o expoente for negativo , vc tem que inverter a fração
g)
h)
i)- = - = -
g)
h)
i)- = - = -
erikafsantoss:
obrigado
respondido por:
1
Vamos lá.
Para eliminar o expoente negativo inverte a fração.
g) (5/2)-^3 = (2/5)³ = 2/5.2/5.2/5 = 8/125
h) (-1/2)^-4 = (- 2/1)^4 = -2/1.-2/1.-2/1.-2/1 = 16/1=16
i) - (-5)² = - (-5). (-5) = - (+25) = -25
Bons estudos
Para eliminar o expoente negativo inverte a fração.
g) (5/2)-^3 = (2/5)³ = 2/5.2/5.2/5 = 8/125
h) (-1/2)^-4 = (- 2/1)^4 = -2/1.-2/1.-2/1.-2/1 = 16/1=16
i) - (-5)² = - (-5). (-5) = - (+25) = -25
Bons estudos
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás